Crafting trade and investment accords for sustainable development : Athena's treaties - Cordonier Segger, Marie-Claire, 1973- (Oxford : Oxford University Press, 2021)
International economic law guides and shapes globalisation and the future of the world economy, our human societies, and the Earth. The rules which facilitate trade and investment could defend the interests of Hermes, Greek god of commerce and thieves, or learn to draw inspiration from Athena, goddess of justice, wisdom, and crafts. This volume explores how trade and investment agreements could promote more sustainable development, rather than increasing the negative social and environmental impacts of economic growth.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 7, 2021).
Keywords: Commercial treaties -- Environmental aspects; Foreign trade regulation; Investments -- Law and legislation; Sustainable development